Changes in Women’s Condom Use over the First Year of College - Walsh, Jennifer L. (2012)
Most college students are sexually active, engage in serially monogamous relationships, and use condoms inconsistently. Little is known about how condom use changes during college and even less about variables predicting changes in use. We used latent growth modeling (LGM) to examine changes in condom use during the first year of college among 279 women (M(age) = 18.0, 74% White) who provided monthly reports on condom use frequency. At study entry, participants also reported on theoretically-suggested risk and protective factors. We examined predictors of changes in use after controlling for use of alternative contraception and partner type. LGMs showed that women decreased their condom use during the first year of college. Levels of condom use were lower initially among women with strong alcohol-sexual risk expectancies, women with more previous sexual partners, women who did not smoke marijuana, and African-American women. Decreases in condom use were greater among women with lower GPAs, women from lower SES families, and women who engaged in binge drinking. Reductions in condom use may place women at greater risk of unplanned pregnancy and sexually transmitted infections. Identification of factors associated with decreases in condom use will enable targeted educational and intervention efforts.